Moringa oleifera ethyl acetate fraction ameliorated the pathophysiological and histopathological alterations induced by Naja katiensis venom - Akindele Oluwatosin Adeyi; Babafemi Siji Ajisebiola; Olubisi Esther Adeyi; Olamiposi Saheed Badru; Osamudiamen Paul; Babatunde Idowu (Elsevier, 2021)
Background: Envenoming by Naja katiensis is known to constitute serious medical challenge. Moringa oleifera is a medicinal plant which have been reported as antivenom agent against pathologies caused by different snakes species. However, the ameliorative effects of extract and fractions of M. oleifera against toxicities induced by N. katiensis venom remain unreported. Purpose: This study therefore investigated the ameliorative effects of n-hexane and ethyl acetate fractions obtained from ethanol extract of M. oleifera leaves against N. katiensis venom-induced physiological and histological pathologies. Methods: Histopathology and antiheamorrhagic activity of M. oleifera extract and fractions were studied using albino male Wistar rats while bovine citrated erythrocytes were used to determine the antiheamolytic and anticoagulant effects. High Performance Liquid Chromatography was performed to chemically characterize the most active fraction of M. oleifera found to be most effective against venom-induced pathologies. Results: N. katiensis venom induced severe cellular alterations in the brain, liver and kidney tissues of envenomed untreated rats. However, treatments with the fractions obtained from M. oleifera ethanol extract ameliorated tissue injuries in these organs and the most effective was ethyl acetate fraction. M. oleifera extract and fractions showed a dose dependent inhibitory effects on anticoagulant, hemolytic, and heamorrhagic activities of N. katiensis venom. The HPLC analysis of ethyl acetate fraction of M. oleifera leaf led to the identification of two major bioactive constituents as quercetin and kaempferol. Conclusion: This study proved that the ethyl acetate fraction of M. oleifera could serve as a potential source of effective compounds against N. katiensis venom-induced pathologies.